Indetifikasi Masalah pada Pekerjaan Pier : Studi Kasus: Proyek Fly Over Akses D.I Panjaitan Stasiun Halim - Pradana, Okkey (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
In the context of architecture and construction, "column pier" is a term that refers to vertical structural elements whose function is to support loads and transmit them to the foundation below. Basically, a column pier is a vertical cantilever structure that supports loads from the floor or structure above and ensures that these loads are safely distributed to the ground through the foundation. Pillar columns are generally made of concrete or steel, depending on the design requirements and loads applied to the structure. They are often used in high-rise buildings, bridges, wharves and other construction structures that require strong vertical support. Pillar columns usually have a cylindrical or rectangular shape with dimensions appropriate to the design stresses and structural loads they must bear. They are one of the important elements in the structural system that provides stability and security to the building or structure.